Spectral Subtraction based Speech De-noising using Adapted Cascaded Median Filter - Nitnaware, Dhiraj (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a new method is proposed for improvement of speech which is distorted by acoustic noise. Acoustic noise reduction is done through a proposed post processed adapted cascaded median filter based on spectral subtraction technique. This method use two stages of filter, in which background noise is eliminated by first stage cascaded median filter and then output speech is post processed by second stage adaptive filter, to reduce musical and residual noise. Proposed post processing algorithm is compared to conventional single stage cascaded median filter based on subjective listening tests and perception evaluation of speech quality (PESQ) scores. Simulation is done in Matlab-15 and results show that enhanced speech generated by proposed algorithm has better quality than conventional cascaded median filter